Tourism Demand Analysis for Marine Ecotourism Management in Kukup Beach, Gunung Kidul, Yogyakarta - Amalia Febryane Adhani Mazaya; Jussac Maulana Masjhoer; Adinda Ariska Pramesit (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Kukup Beach is one of the beaches in Gunung Kidul, Yogyakarta whose management is still in the developing stage. However, the demand for marine tourism is quite busy with the lack of studies and research on the potential and analysis of management recommendations for Kukup Beach. The aim of the research is to analyze tourism demand for managing marine ecotourism at Kukup Beach. The research was conducted in May 2023 at Kukup Beach using a structured questionnaire data collection method and the number of respondents was 103 people. Data analysis uses multiple linear regression statistics and descriptive analysis of ecotourism development. The results obtained are that the characteristics of Kukup beach tourists form a pattern with dominant tourists of productive age (18-30 years), female with a relatively high level of education. Tourist visits are influenced by travel cost, gender, income, education, age, and distance. The tourism demand function is obtained as follows y = 6.223-5.20-07c-0.767g+1.31-06i-0.508e-0.060a-0.783d. Management of Kukup Beach tourism using Ecotourism principles pays attention to visit management considering the characteristics of young tourists, it applies travel rules in accordance with conservation principles. In this way, Kukup Beach ecotourism management can develop and be sustainable.